The effect of weathering aging on the color and roughness values of wood material impregnated with phase change materials with increased UV resistance - Can, Ahmet (Bursa Technical University, 2023)
This study aimed to increase the resistance of hybrid poplar (Populus x euroamericana) wood to UV rays that it may be exposed to in above-ground areas. For this reason, poplar wood samples were impregnated using lauric acid (C12H24O2), myristic acid (C14H28O2), and shellac polymer. The samples obtained were subjected to 400 hours of accelerated aging. The total color change (?E) of the samples was evaluated at 100, 200, and 400 hours after starting the test. In these examples, there was an increase in ?L* values of the variations without shellac (control, MA1, MA2, LA1, LA2) in the first 100 hours of the test period and a decrease in later times (200-400 hours). In contrast, the ?a* and ?b* values in the first 100 hours while there was a negative trend, an increase was observed in the positive direction at 200 and 400 hours. While an increased total color change (?E*) occurred in the early stages of the accelerated aging test, the color change decreased later. At the end of the 400 hours accelerated aging test, a total color change of 13.65 in the control samples and 14.54 in the shellac polymer was obtained. In contrast a lower total color change was obtained in the other variations. The minimum total color change of 2.95 was obtained in the MA2Sh group.

Bu çalışmada, melez kavak (Populus x euroamericana) odununun toprak üstü kullanım yerlerinde maruz kalabileceği UV ışınına karşı direncinin arttırılması amaçlanmıştır. Bu sebeple kavak odun örnekleri laurik asit (C12H24O2), miristik asit (C14H28O2) ve şellak polimeri kullanılarak emprenye edilmiştir. Elde edilen örnekler toplam 400 saat hızlandırılmış yaşlandırma işlemine maruz bırakılmıştır. Örneklerin teste başladıktan 100, 200, ve 400 saat sonra toplam renk değişimi (?E) değerlendirilmesi yapılmıştır. Bu örneklerde, test süresinin ilk 100. saatinde şellak kullanılmayan (kontrol, MA1, MA2, LA1, LA2) varyasyonların ?L* değerlerinde artma, ilerleyen sürelerde (200-400 saat) ise azalmalar, buna karşın ?a* ve ?b* değerlerinde ilk 100 saat negatif yönde bir eğilim söz konusu iken, 200 ve 400 saatlerde ise pozitif yöne doğru bir artış gözlenmiştir. Hızlandırılmış yaşlandırma testinin ilk zamanlarında artma toplam renk değişimi (?E*) oluşurken, ilerleyen zamanlarda renk değişimi azalmıştır. 400 saat hızlandırılmış yaşlandırma testi sonunda kontrol örneklerinde 13,65, şellak polimerinde 14,54’lük toplam renk değişimi elde edilirken, diğer varyasyonlarda daha düşük toplam renk değişimi elde edilmiştir. Minimum toplam renk değişimi 2,95 ile MA2Sh grubunda elde edilmiştir.
UV direnci arttırılmış faz değiştiren malzemeler ile emprenye edilmiş ahşap malzemenin renk değerleri üzerine hızlandırılmış UV yaşlandırmanın etkisi
Keywords: Wood Protection Technology; Odun Koruma Teknolojisi